2021
DOI: 10.1044/2020_jslhr-20-00325
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Gray Matter Volume Variations and Energy Utilization in the Brain: Implications for Developmental Stuttering

Abstract: Purpose The biological mechanisms underlying developmental stuttering remain unclear. In a previous investigation, we showed that there is significant spatial correspondence between regional gray matter structural anomalies and the expression of genes linked to energy metabolism. In the current study, we sought to further examine the relationship between structural anomalies in the brain in children with persistent stuttering and brain regional energy metabolism. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A correlation was found for two out of four genes. Similarly, Boley et al ( 2021 ) correlated the pattern of gray matter differences with the normal pattern of cerebral glucose metabolism. A correlation of 0.36 was found for the left hemisphere.…”
Section: Discussionmentioning
confidence: 97%
“…A correlation was found for two out of four genes. Similarly, Boley et al ( 2021 ) correlated the pattern of gray matter differences with the normal pattern of cerebral glucose metabolism. A correlation of 0.36 was found for the left hemisphere.…”
Section: Discussionmentioning
confidence: 97%
“…The dopaminergic neurons have also been reported to have greater energy demands ( Pacelli et al, 2015 , Pissadaki and Bolam, 2013 ). It has been reported that brain areas with high energy demands coincide with those areas that are significantly different in brain anatomy in stuttering ( Chow et al, 2020 , Boley et al, 2021 ) (see review in Alm, ( Alm, 2021 )) and these undergo rapid growth during early childhood. The high metabolic demands in the dopamine system during dynamic periods of neurodevelopment, combined with possible deficits in connections among circuits that enable learning and execution of automatized motor sequences such as is the case in speech, may be affected in stuttering starting close to stuttering onset.…”
Section: Discussionmentioning
confidence: 99%